(3aVGFd HjJ GdebOS hGdNdjd haVGFd GdTGes - (3CHh GdeYGdj eTQa Hf eQLj Hf EHQGgje GdebOSj, GHf eQLjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdCQV hGNJGQ efgG s
(3BNQgG (B:s
(3jG ChQTdje CfJ ebOS HfhQi hajc GdeMTQ s
(3GfXQ GdbSe GdChd Qbe (B366s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B227s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B228 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs